2015
DOI: 10.1111/jphp.12418
|View full text |Cite
|
Sign up to set email alerts
|

The enantioselective population pharmacokinetics of intravenous ketorolac in children using a stereoselective assay suitable for microanalysis

Abstract: Only body weight influenced the PK parameters for R(+) and S(-) ketorolac. Using allometric size scaling significantly affected the clearances (CL, Q) and volumes of distribution (V1 , V2 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Previous studies in different patient groups have reported significantly higher pharmacokinetic parameters for the S‐ than the R‐enantiomer . In the current study, similar patterns were found: the typical clearance value of the S‐enantiomer was over threefold higher compared with the R‐enantiomer.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in different patient groups have reported significantly higher pharmacokinetic parameters for the S‐ than the R‐enantiomer . In the current study, similar patterns were found: the typical clearance value of the S‐enantiomer was over threefold higher compared with the R‐enantiomer.…”
Section: Discussionsupporting
confidence: 88%
“…Data from three previously published studies of the pharmacokinetics of intravenous ketorolac in children were combined to assess the population pharmacokinetics of an intravenous bolus of ketorolac (0.5 mg . kg −1 ) administered for postoperative analgesia after elective surgery to children aged 2 months to 16 years …”
Section: Methodsmentioning
confidence: 99%
“…Following ethical approval by the North of Scotland Research Ethics Committees and authorization by the Medicines and Healthcare products Regulatory Agency‐UK, eleven children (aged 1.7‐15.6 years, weight 10.7‐67.4 kg, height 83‐165 cm, BMI 15.5‐32.1 kg . m −2 ) undergoing elective day case surgery were recruited for the pharmacokinetic analysis of intravenous ketorolac R(+) and S(−) enantiomers . General anesthesia was induced either intravenously with 3.5 mg .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is our inability to include all published datasets in children. 13,26,27 Based on a systematic search, we identified and contacted all relevant research groups with data in children, and provided them with access to the study protocol.…”
Section: Simulations To Investigate the Contribution Of S-ketorolacmentioning
confidence: 99%